Pengembangan Media Pembelajaran Wordwall Pada Pelajaran Kimia Materi Hukum Dasar Kimia di SMA Kr. Eben Haezar Manado - Charold Septiano Paulus; Soenandar M.T. Tengker; Jeanne M. Tuerah (Oxygenius: Journal Of Chemistry Education, 2023)
This study aims to develop new learning media using wordwall in chemistry learning, especially in the basic chemical law material at SMA Kr. Eben Haezar Manado, class X. Another objective is to evaluate the feasibility of learning media wordwall in the context of learning chemistry on basic legal material at the school. The research method used is the R&D (Research and Development) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Wordwall learning media was developed and implemented in chemistry learning in class X at SMA Kr. Eben Haezar Manado. This study provides several results, namely; The wordwall learning media that was developed received a positive response from students in class X at SMA Kr. Eben Haezar Manado. This media is considered feasible and can be used in chemistry learning basic legal material based on the validity test taken. This research has important implications in increasing the use of wordwall learning media in chemistry learning at SMA Kr. Eben Haezar Manado class X. The use of this media can increase student engagement, facilitate understanding of chemistry concepts, and improve problem solving skills. It is suggested that wordwall learning media can be integrated into the broader chemistry learning strategy in this school.